Tuberculous meningitis masquerading as acute ischemic stroke in young adult - Patil, Divya V.; K., Jeyapalan; A., Mohamed Kasim (International Journal of Research in Medical Sciences, 2020)
Tubercular meningitis (TBM) constitute 5% of all cases of extra pulmonary tuberculosis but a presentation leading to an ischemic stroke in a young adult is a rare clinical entity. In a case of TB vasculopathy, vasculitis, venous thrombosis and aneurysm may be the underlying events leading to a stroke. Stroke in TBM is seen in the tubercular zone which encompasses internal capsule, thalamus and caudate nucleus. Inflammatory mediators like TNF alpha, Interferon gamma and vascular endothelial growth factor have been implicated in the pathogenesis of arteritis. Imaging modalities like MRI show lesions which are usually bilateral in the territory of the perforating vessels. We report a case of 24 year old Asian male who presented with complaints of headache, projectile vomiting and altered sensorium. On examination his Glasgow Coma Scale (GCS) was 10/15, with left oculomotor and left facial nerve palsy, and hypotonia of all 4 limbs with bilateral plantar reflexes being mute. Contrast MRI of brain showed acute infarct, meningeal enhancement and basal exudates. He was started on Anti-tubercular therapy and steroids, but had a poor clinical outcome, due to his late presentation.